FRI0010 Disruption of dominant B-cell/plasma cell clones in rheumatoid arthritis synovium by rituximab correlates with treatment response. (23rd January 2014) - Doorenspleet, M.E.; Klarenbeek, P.L.; Boumans, M.J.; Thurlings, R.M.; Esveldt, R.E.; van Schaik, B.D.; van Kampen, A.H.; Gerlag, D.M.; Baas, F.; Tak, P.P.; Plenge, R.M.; de Vries, N.
Abstract : Background: Autoreactive B-lymphocytes are thought to play an important role in rheumatoid arthritis (RA). B-cell depletion therapy by rituximab (RTX) has shown that targeting the humoral immune response can result in clinical improvement. Unfortunately, the depletion is transient and might result in disease relapse. Hence, analysis of the B-cell/plasma cell compartment in synovium (ST) in patients undergoing RTX therapy might help to identify autoreactive cells responsible for disease persistence and relapse. Objectives: To compare the B-cell/plasma cell repertoire in ST at baseline, 4 weeks and 16 weeks after RTX treatment using a newly developed next-generation sequencing protocol. Methods: Eleven RA patients were included and treated with two intravenous infusions of 1000mg RTX without additional methylprednisolone. At baseline, all patients fulfilled ACR criteria for RA, were ACPA+ and had a DAS28score >3.2. At week 24, nine patients demonstrated moderate to good EULAR responses. mRNA was isolated from consecutive samples and full-repertoire analysis of the immunoglobulin heavy-chain was performed with primers for all V(ariable)-genes. All amplified products encode the CDR3, a unique sequence that defines a unique clone. The number of sequences reflects the amount of immunoglobulins produced by that clone and can be used as a measure for "dominance" of that particular clone. The samples were analyzed using GS-FLX/454 and custom bioinformatics algorithms (>10, 000 sequences/sample). Clones with a frequency of >0, 5% were arbitrarily considered as dominant clones. Results: Synovial clones were detected in all patients in equal numbers at baseline and 4 weeks after RTX. However, after 16 weeks the number of dominant clones significantly increased compared to baseline (mean +55, 3%, p=0.04). In line, there was a significant decrease in the number of non-dominant clones compared to baseline (mean -47.7%, p=0.03). In 5 patients 17, 9% of the dominant clones at baseline was detectable after 16 weeks (mean, SD 8, 0%), half of these clones were dominant at both time points (mean 8, 8%, SD 4, 6%). In the remaining 6 patients dominant clones at baseline were not at all retrieved after 16 weeks. Interestingly, the latter group showed better treatment responses determined by a decrease in DAS28score (-0.84 (SD 0.48) and -2.1 (SD 0.88) DAS28 points resp., p=0.01). Conclusions: Our observations suggest a disruption of dominant clones and a repopulation of distinctly different clones in synovium 16 weeks after rituximab. The persistence of dominant clones was associated with decreased treatment response. Further study of persisting dominant clones, especially during disease relapse, might help to identify and characterize disease-associated B-cells and/or plasma cells. Disclosure of Interest: None Declared